Herbert Putnam papers - Putnam, Herbert, 1861-1955.; Jacobi, Mary Putnam, 1842-1906.; O'Hara, Eliot, 1890-1969.; O'Hara, Shirley Putnam, 1886-; Pinhey, Amy Putnam; Putnam, Brenda, 1890-1975.; Putnam, Charlotte Elizabeth Munroe, -1928.; Putnam, C. H. (Catherine Hunt), 1792-; Putnam, George Palmer, 1814-1872.; Putnam, Israel, 1718-1790.; Putnam, Ruth, 1856-1931.
Correspondence, diaries, journals, speeches, articles, legal records, genealogical material, autograph collection, printed matter, and scrapbooks relating chiefly to Putnam's family and personal life. Includes correspondence, diaries, and journals of members of the Putnam and allied Mason, O'Hara, and Pinhey families. Also includes papers pertaining to Putnam's interests and activities in the field of librarianship, especially as director of the Boston Public Library and Librarian of Congress. Subjects include the purchase by the Library of Congress of the Otto Vollbehr Collection of incunabula and the establishment of the Library of Congress Trust Fund Board. Family members represented include his grandmother, C.H. Putnam; father, George Palmer Putnam; sisters, Amy Putnam Pinhey, Mary Putnam Jacobi, and Ruth Putnam; wife, Charlotte Elizabeth Munroe Putnam; daughters, Brenda Putnam and Shirley Putnam O'Hara; son-in-law, Eliot O'Hara; and Israel Putnam, Revolutionary War general. Correspondents include James Truslow Adams, Charles William Eliot, Luther Harris Evans, Worthington Chauncey Ford, Waldo Gifford Leland, Archibald MacLeish, Agnes Elizabeth Ernst Meyer, Charles Moore, Frederick Law Olmsted, Jr., Theodore Roosevelt, Ainsworth Rand Spofford, and Egerton Swartwout.
Library of Congress Prints and Photographs Division.
Librarian of Congress, 1899-1939. Full name: George Herbert Putnam.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Collection related to the Library of Congress Archives.
Keywords: Adams, James Truslow, -- 1878-1949 -- Correspondence; Eliot, Charles William, -- 1834-1926 -- Correspondence; Evans, Luther Harris, -- 1902-1981 -- Correspondence; Ford, Worthington Chauncey, -- 1858-1941 -- Correspondence; Leland, Waldo Gifford, -- 1879-1966 -- Correspondence; MacLeish, Archibald, -- 1892-1982 -- Correspondence; Meyer, Agnes Elizabeth Ernst, -- 1887-1970 -- Correspondence; Moore, Charles, -- 1855-1942 -- Correspondence; Olmsted, Frederick Law, -- 1870-1957 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Spofford, Ainsworth Rand, -- 1825-1908 -- Correspondence; Swartwout, Egerton, -- 1870-1943 -- Correspondence; Vollbehr, Otto H. F. -- 1869-; Mason family; O'Hara family; Pinhey family; Putnam family; Boston Public Library; Library of Congress; Library of Congress -- Officials and employees; Library of Congress. -- Trust Fund Board; Otto Vollbehr Collection (Library of Congress); Autographs -- Collections; Incunabula; Libraries -- Massachusetts -- Boston; Libraries -- Washington (D.C.); Library science; Librarians of Congress